2020
DOI: 10.1007/s11270-020-04683-y
|View full text |Cite
|
Sign up to set email alerts
|

Analysing Contaminant Mixing and Dilution in River Waters Influenced by Mine Water Discharges

Abstract: Mine water discharges can cause negative effects on recipient rivers. The magnitude of the effects depends on how quickly and efficiently contaminants dilute in the river. Electrical conductivity (EC) is linked to the water quality and can be utilized as a general tool to compare and detect the contaminant sources and concentration changes derived from mine water discharge. Hydrological and flow velocity profiling devices were tested to assess the impact as well as mixing and dilution of mine effluent discharg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Finally, SO 4 presents, in general, the best performance regarding the conservative mixing approach. This behavior was rather expected as sulfate is recognized as a constituent that is not greatly affected by changes in pH or removed by precipitation or sorption processes (Turunen et al, 2020). In fact, in two of the three sectors (1 and 3), values of RRMSE are less than 15%, and the values of E and E 1 are greater than 0.4, even reaching 0.97 (E in Sector 3), which confirms its more conservative behavior.…”
Section: Analysis By Parametermentioning
confidence: 52%
See 1 more Smart Citation
“…Finally, SO 4 presents, in general, the best performance regarding the conservative mixing approach. This behavior was rather expected as sulfate is recognized as a constituent that is not greatly affected by changes in pH or removed by precipitation or sorption processes (Turunen et al, 2020). In fact, in two of the three sectors (1 and 3), values of RRMSE are less than 15%, and the values of E and E 1 are greater than 0.4, even reaching 0.97 (E in Sector 3), which confirms its more conservative behavior.…”
Section: Analysis By Parametermentioning
confidence: 52%
“…On the other hand, for constituents such as As and Fe, it is verified that more complex approaches coupling hydrologic transport to chemical reactions are required, considering specific issues such as pH control, removal rates, residence times, and transient storage (Caruso et al, 2008;Kimball et al, 1994). However, even under the limitations described, the fact that the simple, conservative mixing model works for SO 4 is a valuable result, as this constituent is known to be one of the primary indicators for detecting mine-related contamination processes in rivers, even before changes in acidity (pH) take place (Turunen et al, 2020). Moreover, such an approach could be a useful starting point for further evaluations of the indirect effect, over water quality, of changes in river's streamflows (provided local streamflowconcentration relationships are known).…”
Section: Final Remarksmentioning
confidence: 99%
“…In addition to the influence of Industries and Dying plants that immediately drain wastewater to the rivers without treatment, there is also a low flow of water coming from the Dhaleshwari River into the marshes. As a result of this action to dilute wastewater, the rivers have been labeled as organically contaminated wetlands, which is thought to be the reason for their poor quality ( 81 ).…”
Section: Resultsmentioning
confidence: 99%
“…It could be observed that there was a minor decrease in contamination level in river water during post-monsoon compared to pre-monsoon season at most of the sampling locations. This decrease in the contamination level might be due to dilution of river water that occurred during the monsoon months (Lasagna et al 2013;Turunen et al 2020).…”
Section: Assessment Of Heavy Metal Contaminationmentioning
confidence: 99%
“…During the analysis, composite data matrices of heavy metal concentration were difficult to illustrate, interpret and draw meaningful conclusions. Therefore, principal component analysis (PCA) is performed to simplify the interpretation of complex data matrices of water quality and the ecological status of any river (Mishra et al 2018;Turunen et al 2020;. PCA has been carried out to identify the possible input sources of heavy metal contaminants in the Hindon River.…”
Section: Introductionmentioning
confidence: 99%